Necessity And Obligation to Organize Internal Control Management - Rareş Cosmin NICORICI; Anatol Melega (Communications of International Proceedings, 2022)
Internal control is closely related to the management of the organization, accounting and human resources within the institution.  The evolution and direction in which the economy and technology are heading exponentially increased, which has led to an increasing complexity of internal control, to new methods and techniques of controlling the activity of economic entities in Romania and beyond.  For a better understanding of the implication of internal control in terms of the public and private sector, we have structured the article in the following parts: (a) the need to implement internal management control; (b) SWOT analysis of SJU Botoşani; (c) the legislation to which the medical establishment relates; (d) econometric analysis of expenditure financed from the budgets of local and central public authorities as well as of revenues from the provision of services; (e) conclusions.
Keywords: internal managerial control; control practices; public entity